2020
DOI: 10.1186/s43166-020-00033-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy versus musculoskeletal mesotherapy for Achilles tendinopathy in athlete

Abstract: Background Achilles tendinopathy (AT) is considered the commonest tendon pathology, occurring mainly in athletes. Different conservative treatment options have been introduced but with short-term effects; however, extracorporeal shockwave therapy (ESWT) and mesotherapy (MT) injections were claimed to provide longer effects and could be used in cases failure of response to conservative treatments. The objective of our prospective 12-week study was to compare the effect of ESWT and MT on chronic Achilles tendino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In an RCT of athletes with high risk of bias comparing ESWT with mesotherapy in Achilles tendinopathy (insertional and non-insertional), both four sessions of ESWT and mesotherapy (microinjections with a mixture composed of betamethasone, normal saline and lidocaine along the tendon) improved VAS and AOFAS hindfoot scores at 4 and 12 weeks without between-group difference. ESWT group showed further improvement in tendon thickness, heterogeneity and calcifications at 12 weeks while mesotherapy reporting improvement limited to tendon thickness 68. In another RCT with high risk of bias including recreationally active individuals with non-insertional Achilles tendinopathy, three sessions of R-SWT resulted in greater reduction in activity-related pain compared with ultrasound therapy or placebo ultrasound (VAS mean and SD 1.42±1.32, 2.85±2.03 and 4.23±1.5, respectively) 69…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In an RCT of athletes with high risk of bias comparing ESWT with mesotherapy in Achilles tendinopathy (insertional and non-insertional), both four sessions of ESWT and mesotherapy (microinjections with a mixture composed of betamethasone, normal saline and lidocaine along the tendon) improved VAS and AOFAS hindfoot scores at 4 and 12 weeks without between-group difference. ESWT group showed further improvement in tendon thickness, heterogeneity and calcifications at 12 weeks while mesotherapy reporting improvement limited to tendon thickness 68. In another RCT with high risk of bias including recreationally active individuals with non-insertional Achilles tendinopathy, three sessions of R-SWT resulted in greater reduction in activity-related pain compared with ultrasound therapy or placebo ultrasound (VAS mean and SD 1.42±1.32, 2.85±2.03 and 4.23±1.5, respectively) 69…”
Section: Resultsmentioning
confidence: 89%
“…In plantar fasciitis, a prospective study found that surgery resulted in better VAS and Roles and Maudsley scores although return to activities tended to be faster with ESWT 55. ESWT appeared to have similar efficacy with mesotherapy when added with exercise programme in Achilles tendinopathy68 but allowed better activity-related pain relief than ultrasound therapy in non-insertional Achilles tendinopathy based on the RCTs 69. In IT band syndrome, ESWT and manual therapy seemed to have comparable outcomes in terms of pain relief and return to activity level when added with an exercise programme 76.…”
Section: Discussionmentioning
confidence: 97%
“…In an RCT that included both midportion and insertional AT, El-Mallah et al found similar improvements in mean Visual Analog Scale (VAS) and American Orthopedic Foot and Ankle Society (AOFAS) hindfoot scores at 4- and 12-wk follow-up between athletes receiving four weekly sessions of combined focused and radial high-energy ESWT ( n = 20) and those receiving weekly mesotherapy injections ( n = 20) (17). In this study, mesotherapy injections were described as 10 to 15 intradermal microinjections of 2 mL of 5-mg betamethasone diproprionate and 2-mg betamethasone sodium phosphate, 2 mL of 0.9% normal saline, and 1 mL of 2% lidocaine.…”
Section: Methodsmentioning
confidence: 94%
“…Compared to mesotherapy, ESWT significantly decreased tendon thickness and improved heterogenicity, Doppler activity, and calcifications at 12-wk (17). Another RCT found no significant difference between sham ( n = 27) and ESWT ( n = 22) for treatment of insertional or midportion AT (18).…”
Section: Methodsmentioning
confidence: 99%
“…Structure was reported in 19% (58/307) of the studies, with neovascularization being the most frequently reported measurement instrument (20 studies) (Table 2; Fig. 2) [20,24,78,82,87,99,135,147,148,170,184,185,191,192,207,287,308,312]. Structure was reported using 21 various outcome measures of tendon morphological, vascular and mechanical properties using diagnostic ultrasound, MRI and other imaging technologies.…”
Section: Structurementioning
confidence: 99%